A Novel Dry Hopping Technology: Kinematic Modelling of a Planetary Rotating Bed Reactor - von Heynitz, Christian; Manuel Stecker, Manuel Stecker; Hofmann, Thomas; Glas, Karl (BrewingScience, 2020)
Dry hopping can be described as a heterogeneous solid-liquid reaction, calling for high mass transfer rates, low resource consumption, and effective phase separation. This work presents a model-based feasibility analysis of a novel approach to dry hopping that addresses these requirements: the planetary rotating bed reactor (PRBR). This solid-liquid reactor is kinematically enhanced by a planetary gear derivate. The superposition of two rotary motions results in an oscillating acceleration that generates a push-back effect on the hop solids contained in the reactor chamber. Clogging of the retaining filter mesh can thereby be prevented while maintaining high relative flow velocities between hop solids and the circulating beer to promote the desired mass transfer. In this work, a 2D simulation model of the system kinematics is implemented in MATLAB?. The model is governed by a set of analytical equations, allowing for high accuracy and low computational effort. Trajectories and accelerations of relevant reactor segments are calculated, considering design and process variables like gear diameter and rotation speed of the input shafts. The existence of the underlying push-back effect and its technical viability are verified and evaluated by appropriate performance indicators in consideration of the fluid throughput. As a result, the PRBR promises to be a fast, hop-saving and fully scalable solution for dry hopping and other heterogeneous reactions.